Determinants of occurrence and survival after sudden cardiac arrest-A European perspective: The ESCAPE-NET project - Empana, Jean-Philippe; Blom, Marieke T; Bӧttiger, Bernd W; Dagres, Nikolaos; Dekker, Jacqueline M; Gislason, Gunnar; Jouven, Xavier; Meitinger, Thomas; Ristagno, Giuseppe; Schwartz, Peter J; Jonsson, Martin; Tfelt-Hansen, Jacob; et al. (Resuscitation, 2018)
AIMS: The ESCAPE-NET project ("European Sudden Cardiac Arrest network- towards Prevention, Education and New Effective Treatments") aims to study: (1) risk factors and mechanisms for the occurrence of sudden cardiac arrest (SCA) in the population, and (2) risk factors and treatment strategies for survival after SCA on a European scale. METHODS: This is an Horizon2020 funded program of the European Union, performed by a European public-private consortium of 16 partners across 10 EU countries. There are 11 deep-phenotyped SCA cohorts for the study of risk factors and treatment strategies for survival after SCA, and 5 deep-phenotyped observational prospective population cohorts for the study of risk factors for occurrence of SCA. Personalized risk scores for predicting SCA onset and for predicting survival after SCA will be derived and validated. RESULTS: The 11 clinical studies with SCA cases comprise 85,790 SCA cases; the 5 observational prospective population cohorts include 53,060 subjects. A total of 15,000 SCA samples will be genotyped for common and rare variants at the Helmholtz Zentrum München (Germany) using the Illumina Global Screening Array which contains > 770,000 SNPs, and after imputation, a database of an estimated > 9 million variants will be available for genome wide association studies. Standardization of risk factors definition and outcomes is ongoing. An Executive Committee has been created along with a Collaboration Policy document. CONCLUSION: ESCAPE-NET will complement ongoing efforts on SCA outside Europe and within Europe including the EuReCa project.
Keywords: kohortové studie; Sudden cardiac arrest; Europe; Out-of-Hospital Cardiac Arrest; náhlá srdeční smrt; zástava srdce mimo nemocnici; Databases, Factual; Humans; rizikové faktory; Risk Assessment; Resuscitation; Emergency Medical Services; urgentní zdravotnické služby; lidé; databáze faktografické; Population Surveillance; Cohort Studies; Death, Sudden, Cardiac; komorbidita; surveillance populace; Risk Factors; Automated external defibrillator; Evropa; Genetics; hodnocení rizik; Comorbidity